TAFSIR TARBAWI MANAJEMEN PENDIDIKAN DALAM AL-QURAN - Ibnurawandhy N. Hula; Yunita ibrahim; Rafli datundugon; Mariaty Podungge (STAI Ma'had Aly Al-Hikam Malang, 2023)
In an Islamic perspective, managerial terms are very popular. However, when approaching the Arabic term here we can mean the individual organization